Dependence of Spreading and Differentiation of Mesenchymal Stem Cells on Micropatterned Surface Area. (20th March 2011) - Song, Wei; Kawazoe, Naoki; Chen, Guoping
Abstract : Micropatterning technology is a highly advantageous approach for directly assessing and comparing the effects of different factors on stem cell functions. In this study, poly(vinyl alcohol)- (PVA-) micropatterned polystyrene surfaces were prepared using photoreactive PVA and ultraviolet photolithography with a photomask. The micropatterned surface was suitable for single-cell array formation and long-term cell culture due to the nanometer thickness of nonadhesive PVA layer. Different degrees of cell spreading with the same cell shape were established by adjusting the sizes of circular, cell-adhesive polystyrene micropatterns. Cell spreading and differentiation of mesenchymal stem cells (MSCs) on the micropatterns were investigated at the single-cell level. The assembly and organization of the cytoskeleton were regulated by the degree of cell spreading. Individual MSCs on large circular micropatterns exhibited a more highly ordered arrangement of actin filaments than did those on the small circular micropatterns. Furthermore, the differentiation of MSCs was dependent on the degree of cell spreading. Increased cell spreading facilitated the osteogenic differentiation but suppressed the adipogenic differentiation of MSCs. This micropatterning method is valuable for stem cell research in tissue engineering and regenerative medicine.